2010
DOI: 10.1080/15427520903558484
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Conservation Agriculture (CA) Systems in Zambia and Zimbabwe to Mitigate Future Effects of Climate Change

Abstract: Most models predict that climate change will affect the southern African region both through temperature rises and increased frequency and severity of drought. Conservation agriculture (CA) based on minimal soil disturbance, crop residue retention, and crop rotations offers potential solutions to mitigate the effects of seasonal drought. In Zimbabwe and Zambia, we investigated the effects of different maize-based CA systems on water relations and crop productivity from 2005-2009 and compared results with conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 8 publications
7
81
1
Order By: Relevance
“…One of these benefits is attributed to the water-harvesting effects of minimum-tillage practices [50,51]. Underwater limited conditions increased soil moisture, leading to comparably higher yields under CA [9]. We did not report any water data in our study but indirectly derived these through sensors that measure related parameters.…”
Section: Implications Of Growing Conditions On Yield Parametersmentioning
confidence: 99%
“…One of these benefits is attributed to the water-harvesting effects of minimum-tillage practices [50,51]. Underwater limited conditions increased soil moisture, leading to comparably higher yields under CA [9]. We did not report any water data in our study but indirectly derived these through sensors that measure related parameters.…”
Section: Implications Of Growing Conditions On Yield Parametersmentioning
confidence: 99%
“…As previously discussed, while growing season temperatures may not increase above the threshold temperatures for sub-tropical and tropical maize by 2050, the higher growing season temperatures will increase plant transpiration thereby increasing planting water use and reducing plant-available soil water. Improved soil water status has the potential to both buffer plants against the potential effects of drought stress under intermittent rainfall and reduce the severity of a drought event (Thierfelder and Wall 2010). Conservation agriculture is a system of agronomy based on minimum soil disturbance through ploughing, residue retention and crop rotations (Hobbs 2007).…”
Section: Reducing the Effects Of Climate Change On Farmers In Maize-bmentioning
confidence: 99%
“…Verhulst et al (2011) showed that, under mild drought, yields of maize grain under conservation agriculture were 1.8 to 2.7 times higher than under conventional management practices. Higher soil water content under conservation agriculture may be an important mechanism by which maize production is buffered against short drought periods during the growing season (Fischer et al 2002;Thierfelder and Wall 2009;Thierfelder and Wall 2010).…”
Section: Reducing the Effects Of Climate Change On Farmers In Maize-bmentioning
confidence: 99%
“…As part of the relief and recovery programs, research and development initiatives have seen the introduction of a specific set of technology options that aim to improve and stabilize crop yields while preserving soil and water, and using precision methods to apply inputs. This set of technology options is defined as conservation agriculture (CA) (Thierfelder and Wall, 2010;Twomlow et al, 2008).…”
Section: Rationale For Conservation Agriculturementioning
confidence: 99%